Case Report: Alzheimer's Dementia Associated With Cerebrospinal Fluid Neurochondrin Autoantibodies - Hansen, Niels; Malchow, Berend; Teegen, Bianca; Wiltfang, Jens; Bartels, Claudia (Frontiers in Neurology, 2022)
Background Neurochondrin autoimmunity is a rare disorder mainly associated with cerebellar and vestibular syndromes. Our report aims to enlarge its phenotypic spectrum to encompass major cognitive disorder with very late onset never before reported in conjunction with neurochondrin antibodies. Methods We describe the case of an 85-year-old woman who presented in our memory clinic. Retrospective analysis of patient records included cerebrospinal fluid (CSF) analysis, magnetic resonance imaging (MRI), and neuropsychological testing using the CERAD-plus. Results Because of her unknown onset of progressive cognitive dysfunction in conjunction with speech and language problems, we decided to take an extensive differential diagnostic approach including a search for neural autoantibodies potentially involved in cognitive impairment. Our patient presented serum and CSF neurochondrin autoantibodies. Further CSF analysis revealed elevated tau and ptau 181 protein as well as a reduced Aß42/40 ratio in CSF, thus matching a biomarker profile of Alzheimer's disease (AD). Neuropsychological tests revealed predominant and severe deficits in verbal and visual memory. Her MRI showed reduced parietal and cerebellar brain volume. Discussion Taken together, this case reveals the novelty of a patient with a CSF-based and typical clinical and imaging profile of AD. She is also likely to have neurochondrin autoimmunity, as we detected neurochondrin autoantibodies in her CSF; we therefore diagnosed AD dementia associated with neurochondrin antibodies. Our case expands the spectrum of neurochondrin autoimmunity to disorders involving major cognitive disorder such as AD dementia. Furthermore, we speculate that neurochondrin autoimmunity might have triggered an acceleration of AD symptoms as its onset was reported only after a short 6-month interval via a synergistic or negatively additive hybrid mechanism of action between neurodegeneration and autoimmunity.